Harmonic Reduction in Output of DFIG Based Wind Turbine Using Hybrid Active Filter - Mr. Chirag Arora, Mr. Ravinder Singh Maan, Subhash Swami (International Journal of Advanced Science and Technology, 2020)
Electricity in the modern time has become one of the most important need of the world. There are several sources of electricity present in form of conventional and non conventional sources. But the conventional energy crisis forced the world to prepare for alternate energy source as wind energy system. Installations of wind turbine have been rapidly rising throughout the world, because of simplicity of this system and proliferation of government policies. The annual rate of increase within the wind energy facility is incredibly high and Republic of India is currently the fifth in the world with a put in capability of concerning 21,262 MW. The proposed work shows the reduced harmonic in generated electrical energy by wind connected DFIG system using hybrid active filter with Maximum Power Point Tracking (MPPT). This work has a simulation of Grid Side Control (GSC) and Rotor Side Control (RSC) with hybrid active filter to reduce the harmonics in case of non linear load. MPPT system is used to track that point or value of wind turbine at which DFIG generates the maximum electrical power. The result of this work is showing that the value of harmonics reduced up to 4.96% from 29.66% when non linear load is connected with the system. It also shows that the value of harmonic is 0.14% when non linear load is not connected to the system. Many researches are going on for developing filters which can suppress the level of harmonics more than the Hybrid active power filter. The model for the proposed work is developed in MATLAB R2018a version. The model is drawn in simulink part of the MATLAB Software.